Aplikasi SI DITA Berbasis Android terhadap Peningkatan Motivasi Orangtua Melakukan Stimulasi Deteksi Dini Tumbuh Kembang - Rizka Adela Fatsena; Djauhar Ismail; Ekawaty Lutfia Haksari; Dewi Rokhanawati (JURNAL KESEHATAN REPRODUKSI, 2021)
Background: Every parent needs to have the skills to carry out monitoring and stimulate the development of infants and children. Technology-based Early Detection and Growth Stimulation is an innovative pathway to providing health informationObjective: To determine the effect of the Android-based Si DITA application to increase parental motivation to stimulate early detection of growth and development in Az-Zahra Early Childhood Education at Sleman RegencyMethod: Quasi Experiment with pretest-post test control group design design patterns. The sample uses the Lemeshow formula with purposive sampling of 15 respondents in each groupResults and Discussion: Obtained p value = 0.001, states that the Android-based Si DITA application to increase parental motivation to stimulate early detection of growth has a meaningful or influential value. The confounding variables that influence are only prior information, while education and income variables have no effectConclusion: Android-based applications can increase parental motivation to stimulate and detect early growth and development